High grade myoepithelial carcinoma of the maxillary si-nus - Patil, Bharati; Hegde, Sushmini; Yadav, Karthik D (International Journal of Dental Research, 2017)
Myoepithelial carcinoma is a rare tumor of salivary glands, the most frequent site being the parotid gland. Myoepithelial carcinoma of the maxillary sinus has only been reported very few times. As the lesion is very rare in the maxillary sinus and due to the lack of specific guidelines for its treatment, its prognosis remains to be poor. We report a rare case of myoepithelial carcinoma in the maxillary sinus and discuss its diagnostic and therapeutic aspects.